Post Irradiation Spindle Cell Carcinoma of Tonsillar Pillar - Prateek Kinra; V. Srinivas; Kavita Sinha; Vibha Dutta (Case Reports in Medicine)
Spindle cell carcinoma of the tonsillar pillar is a rare malignancy. A case of spindle cell carcinoma of the anterior tonsillar pillar in a 59-year-old man is presented. A growth on the anterior tonsillar pillar, measuring 9×7×6 mm, was resected. The neoplasm occurred as a complication of radiotherapy (excessive cumulative radiation dose of 60 Gray) for carcinoma larynx with a latency period of three years. Postradiation spindle cell carcinoma is an uncommon disease manifesting as sarcoma in a previously irradiated field, usually with a latent period of 5 years or more. Literature is limited to small series. Histologically, this tonsillar growth was composed of a squamous cell carcinoma (epithelial component) and a spindle cell sarcomatous component. The two components of the tumour were confirmed using the immunohistochemical staining (cytokeratin and vimentin). Further p53 positivity of the sarcomatous elements aided in ruling out radiation-induced nonmalignant changes of mesenchymal tissue. This paper discusses this rare tumour in a common setting.